Insertion of indigenous students in higher education in Itapua 2021 (UNIHumanitas, 2022)
The research addressed the problems related to indigenous education and the need to promote programs aimed at enabling the indigenous population to have greater participation in their sociocultural environment and in society. The general objective was focused on describing the factors that affect the insertion of indigenous students in the higher level of the educational system in the department of Itapúa in the year 2021. The methodology used was mixed; the type of research used was descriptive. A non-experimental and specifically transectional design was applied. The data were collected between the first and second semesters of the year 2021. Data collection was through interviews and questionnaires. The results showed that it is necessary to implement educational reforms that facilitate the insertion of indigenous students in higher education, since at some point in their education they suffered some type of discrimination, so it is uncommon for an indigenous student to enter university
Keywords: instruction; indigenous; students